1988
DOI: 10.1002/ijc.2910410725
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution, pharmacokinetics and imaging of131I-labelled OC125 in ovarian cancer

Abstract: Fifteen patients with or suspected of having ovarian carcinoma were injected intravenously (i.v.) or intraperitoneally (i.p+) with t3tl-labelled OC 125 F(ab')z. Radioimmunoscintigraphy after i.v. injection revealed 50% of the tumor sites. After i.p. injection all tumor sites were visualized, except in one case in which the antibody remained loculated because of adhesions. One patient with endometrial cancer showed no specific uptake of the antibody after i.p. injection. The serum half-life of the radiolabelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The phase I and phase II trials have shown the potential of 131 I-labelled OC125 antigen-binding fragment as a therapeutic agent. 6567 MUC4 is expressed by the tumour cells of peritoneal effusions in 99% of patients with ovarian cancer, indicating its potential as a target for intraperitoneal radioimmunotherapy. 53 …”
Section: Mucins As Targets For Radioimaging Radioimmunotherapy and mentioning
confidence: 99%
“…The phase I and phase II trials have shown the potential of 131 I-labelled OC125 antigen-binding fragment as a therapeutic agent. 6567 MUC4 is expressed by the tumour cells of peritoneal effusions in 99% of patients with ovarian cancer, indicating its potential as a target for intraperitoneal radioimmunotherapy. 53 …”
Section: Mucins As Targets For Radioimaging Radioimmunotherapy and mentioning
confidence: 99%
“…OC125 is a murine monoclonal antibody that recognizes the cell-surface antigen CA 125, a 1000-kDa glycoprotein (Hosono et al, 1992) expressed by 85% of non-mucinous epithelial ovarian cancers (Karlan et al, 1988). Conjugates of OC125 with radioisotopes (Haisma et al, 1988;Muto et al, 1992) and cytotoxic drugs (Beck et al, 1994) have been administered i.p. to target ovarian cancer in both animals and humans.…”
mentioning
confidence: 99%
“…In addition the use of this promising MAb for diagnostic or therapeutic intraperitoneal applications and for radioimmunoguided surgery sho be investigated [19,[36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%